1998
DOI: 10.1007/s002689900413
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Patterns in Patients Who Undergo Hemofiltration for Treatment of Multiple Organ Failure

Abstract: The excessive uncontrolled activation of inflammatory cells and mediators after trauma or major surgery plays a key role in the development of adult respiratory distress syndrome and multiple organ system failure (MOSF). In the past elevated cytokine levels were shown to influence the outcome of these patients adversely. There are diverging results regarding the removal of circulating cytokines by various methods of hemopurification for clinical improvement of MOSF. Seven patients after trauma or major surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Other clinical studies showed contradictory results on the removal of TNF, although sieving coefficients ranged from 0-52%, plasma TNF levels did not decrease in many clinical studies (Hoffmann and Faist 2001). Koperna et al (1998) even showed an increase of TNF levels during haemofiltration. Moreover, the use of different membranes and haemofiltration devices may result in different TNF elimination rates.…”
Section: Discussionmentioning
confidence: 95%
“…Other clinical studies showed contradictory results on the removal of TNF, although sieving coefficients ranged from 0-52%, plasma TNF levels did not decrease in many clinical studies (Hoffmann and Faist 2001). Koperna et al (1998) even showed an increase of TNF levels during haemofiltration. Moreover, the use of different membranes and haemofiltration devices may result in different TNF elimination rates.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, several studies have shown that CRRT can remove serum systemic inflammatory mediators that contribute to ARDS pathogenesis by convection and absorption. 6 , 16 - 19 …”
Section: Discussionmentioning
confidence: 99%
“…Although plasma levels of these cytokines remained stable, the septic patients' cardiac output and stroke volume normalized just 1 day after starting treatment 3 . Other studies have similar findings, suggesting that cytokine removal by KRT is not clinically significant and that resulting cardiovascular benefits of KRT are not related to cytokine clearance 14–16 . Rather, improvements may be due to the elimination of excess fluid and the resulting hemodynamic stability.…”
Section: Role Of Kidney Replacement Therapy In Sepsismentioning
confidence: 76%